Biological characterization of an injectable platelet-rich fibrin mixture consisting of autologous albumin gel and liquid platelet-rich fibrin (Alb-PRF). (2nd January 2021) - Fujioka-Kobayashi, Masako; Schaller, Benoit; Mourão, Carlos Fernando De Almeida Barros; Zhang, Yufeng; Sculean, Anton; Miron, Richard J.
Abstract: Platelet-rich fibrin (PRF) has been proposed as an autologous membrane with the advantages of host accumulation of platelets and leukocytes with entrapment of growth factors. However, limitations include its faster resorption properties ( 2 weeks). Interestingly, recent studies have demonstrated that by heating a liquid platelet-poor plasma (PPP) layer, the resorption properties of heated albumin (albumin gel) can be extended from 2 weeks to greater than 4 months (e-PRF). The aim of the present study was to characterize the biological properties of this novel regenerative modality. Whole blood collected from peripheral blood in 9-mL plastic tubes was centrifuged at 700 g for 8 minutes. Thereafter, the platelet-poor plasma layer was heated at 75°C for 10 minutes to create denatured albumin (albumin gel). The remaining cells and growth factor found within the buffy coat layer (liquid PRF) were thereafter mixed back together with the cooled albumin gel to form Alb-PRF. Histological analysis, including the distribution of cells within Alb-PRF, was then performed. Seven different growth factor release kinetics from Alb-PRF were characterized up to 10 days, including PDGF-AA, PDGF-AB, PDGF-BB, TGF-β1, VEGF, IGF and EGF. Thereafter, gingival fibroblast cell responses to Alb-PRF were investigated by means of a live/dead assay at 24 hours; migration assay at 24 hours; proliferation assay at 1, 3 and 5 days; real-time PCR for the expression of TGF-β and collagen 1a2 at 3 and 7 days; and collagen 1 immunostaining at 14 days. It was first observed histologically that viable cells were evenly distributed throughout the Alb-PRF formulation. Growth factor release demonstrated a slow and gradual release, particularly for TGF-β1 and PDGF-AA/AB, during the entire 10-day period. Alb-PRF also exhibited statistically significantly higher cell biocompatibility at 24 hours and statistically significantly induced greater fibroblast proliferation at 5 days when compared to those of control TCP. Alb-PRF further induced statistically significantly greater mRNA levels of TGF-β at 3 and 7 days, as well as collagen 1 at 7 days. The present results indicate that Alb-PRF possesses regenerative properties induced by the slow and gradual release of growth factors found in liquid PRF via albumin gel degradation. Future studies are thus warranted to fully characterize the degradation properties of Alb-PRF in vivo and explore future clinical applications in various fields of medicine.